CARD14 Glu138 mutation in familial pityriasis rubra pilaris does not warrant differentiation from familial psoriasis. Issue 2 (1st July 2015) - Inoue, Nana; Dainichi, Teruki; Fujisawa, Akihiro; Nakano, Hajime; Sawamura, Daisuke; Kabashima, Kenji
Abstract: Some familial cases of pityriasis rubra pilaris (PRP) have the CARD14 gene mutations that are also detected in familial psoriasis vulgaris. However, genotype–phenotype correlation in these two entities is poorly understood. Here, we report a case of PRP with a new mutation in CARD14 . Genomic analysis of a 40‐year‐old female patient with sporadic PRP type V identified a heterozygous dominant c.412G>A mutation (p.Glu138Lys) in CARD14 . Two types of CARD14 mutations causing Glu138 substitutions have been reported in cases of familial PRP and pustular psoriasis. All three types, including the present case, are predicted to cause similar loss of the negative charges at this site. This suggests that the difference in molecular charge and the resulting change in molecular interaction around the N‐terminal end of the coiled‐coil region of CARD14 molecule do not determine the phenotypic differences between psoriasis and PRP.